Essential role of Salmonella Enteritidis DNA adenine methylase in modulating inflammasome activation - Yaxin Guo; Dan Gu; Tingting Huang; Liyan Cao; Xinyu Zhu; Yi Zhou; Kangru Wang; Xilong Kang; Chuang Meng; Xinan Jiao; Zhiming Pan (BMC Microbiology, 2020)
Abstract Background Salmonella Enteritidis (SE) is one of the major foodborne zoonotic pathogens of worldwide importance which can induce activation of NLRC4 and NLRP3 inflammasomes during infection. Given that the inflammasomes play an essential role in resisting bacterial infection, Salmonella has evolved various strategies to regulate activation of the inflammasome, most of which largely remain unclear. Results A transposon mutant library in SE strain C50336 was screened for the identification of the potential factors that regulate inflammasome activation. We found that T3SS-associated genes invC, prgH, and spaN were required for inflammasome activation in vitro. Interestingly, C50336 strains with deletion or overexpression of Dam were both defective in activation of caspase-1, secretion of IL-1β and phosphorylation of c-Jun N-terminal kinase (Jnk). Transcriptome sequencing (RNA-seq) results showed that most of the differentially expressed genes and enriched KEGG pathways between the C50336-VS-C50336Δdam and C50336-VS-C50336::dam groups overlapped, which includes multiple signaling pathways related to the inflammasome. C50336Δdam and C50336::dam were both found to be defective in suppressing the expression of several anti-inflammasome factors. Moreover, overexpression of Dam in macrophages by lentiviral infection could specifically enhance the activation of NLRP3 inflammasome independently via promoting the Jnk pathway. Conclusions These data indicated that Dam was essential for modulating inflammasome activation during SE infection, there were complex and dynamic interplays between Dam and the inflammasome under different conditions. New insights were provided about the battle between SE and host innate immunological mechanisms.